Reigion: past, present and future - Farley, Guy Francis (My University, 1898)
Introduction: Man is a dependent being. As far back as we can find any history, authentic on traditional, there is embodied in him a religious or superstitious feeling of love, fear, and worship for some supreme, material or spiritual power. Religion is inseparable from the man; it is a part of his nature, and must in some way express itself in his life. No matter how irreligious he may claim to be, or believe himself to be, there is no man of normal mind, but has this feeling of reverential dependency upon some power above and beyond himself. In spite of this universality of feeling, no two men have the same religious belief, no two men have exactly the same manner of expressing their reverence and devotion.
Citation: Farley, Guy Francis. Reigion: past, present and future. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Man; History; Religion; Reverence; Religious Belief; Theses; Manuscripts (documents)